2021
DOI: 10.3390/pathogens10121616
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Ribavirin against Tilapia tilapinevirus in Fish Cells

Abstract: The outbreak of the novel Tilapia tilapinevirus or Tilapia lake virus (TiLV) is having a severe economic impact on global tilapia aquaculture. Effective treatments and vaccines for TiLV are lacking. In this study, we demonstrated the antiviral activity of ribavirin against TiLV in E-11 cells. Our findings revealed that at concentrations above 100 μg/mL, ribavirin efficiently attenuates the cytopathic effect of the TiLV infection in fish cells. When administered in a dose-dependent manner, ribavirin significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Previous research have demonstrated the susceptibility of various cell lines to TiLV infection, including E-11 cells, a cloned cell line derived from striped snakehead ( Channa striatus , SSN-1) cell line ( Iwamoto et al, 2000 ; Lertwanakarn et al, 2021 ), and primary tilapia ( Oreochromis spp.) cell lines isolated from the brain, heart, and liver ( Eyngor et al, 2014 ; Li et al, 2022a ; Li et al, 2022b ; Yadav et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research have demonstrated the susceptibility of various cell lines to TiLV infection, including E-11 cells, a cloned cell line derived from striped snakehead ( Channa striatus , SSN-1) cell line ( Iwamoto et al, 2000 ; Lertwanakarn et al, 2021 ), and primary tilapia ( Oreochromis spp.) cell lines isolated from the brain, heart, and liver ( Eyngor et al, 2014 ; Li et al, 2022a ; Li et al, 2022b ; Yadav et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TiLV can multiply and lead to cell death in various fish cell lines ( Eyngor et al, 2014 ; Lertwanakarn et al, 2021 ; Li et al, 2022a ; Thangaraj et al, 2018 ; Wang et al, 2018 ; Yadav et al, 2021 ). A recent study by Lertwanakarn et al (2021) revealed that TiLV infection caused cytopathic effect (CPE) in E-11 cells within 3 days, while CPE formation in other cell lines may vary between 3 to 11 days post-infection (dpi) ( Li et al, 2022a ; Thangaraj et al, 2018 ; Wang et al, 2018 ; Yadav et al, 2021 ). Transmission electron microscopy (TEM) has revealed that TiLV particles are rounded in shape and approximately 60–110 nm in size ( Eyngor et al, 2014 ; Li et al, 2022a ; Piewbang et al, 2022 ; Thangaraj et al, 2018 ; Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…TiLV is now defined as a new species, Tilapia tilapinevirus , in the Tilapinevirus genus, within the Amnoonviridae family, which together with the Orthomyxoviridae , form the Articulavirales order 6 . Whilst the phylogeny of different isolates 7 , detection and pathogenesis of the virus and possible treatments by vaccination 8 or drugs 9 are now being extensively studied, the molecular virology of TiLV is poorly understood, partly due to the current lack of reverse genetics or minigenome systems 10 . In addition, the uniqueness of the putative TiLV encoded proteins, apart from a recognisable polymerase PB1-like subunit, precludes hypotheses as to protein function based on sequence homology or structure prediction using Alphafold 11 or RoseTTAfold 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the phylogeny of different isolates 5 , detection and pathogenesis of the virus and possible treatments by vaccination 6 or drugs 7 are now being extensively studied, the molecular virology of TiLV is poorly understood, partly due to the current lack of reverse genetics or minigenome systems 8 . In addition, the uniqueness of the putative TiLV encoded proteins, apart from a recognisable polymerase PB1-like subunit, precludes hypotheses as to protein function based on sequence homology or structure prediction using Alphafold 9 .…”
Section: Introductionmentioning
confidence: 99%